Drug Nicknaming in Western Algeria - Labed, Zohra (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2019)
Illegal drug consumption is a long-run issue with a worldwide apprehension. Drug abusers identify themselves differently to remain far from public appearance and escape court institutions. Nicknaming drugs and their different types and forms constitute one way of drug abusing concealment and disguisement. Nicknaming involves a variety of practices that acquire full of positive and/ or negative connotations in society over time. Social practices carry cultural values that shape the nickname giver’s perception of the nickname bearer, a fact that can be reflected in the way the nickname is chosen within various fields. Nickname givers are alone responsible for allocating the exclusionary or inclusionary character to the nickname bearer. The present paper seeks to examine and analyse the various nicknames attributed to diverse types of such psychotropic substances by the Algerians with special reference to the west of multilingual and diglossic Algerian speech community. More particularly, how are drugs nicknamed in western Algeria? Which language varieties are involved in such nicknaming? Why are illegal drugs nicknamed at all? The findings at hand assign nicknames to physicality, mannerism, experience and/ or linguistic adjustments. Drug nicknaming nomenclature under study makes up importantly drug consumers’ secret language in the present setting.